Implementasi Strategi Pengembangan Sosial Emosional pada PAUD Berbasis Karakter: Studi Multi Situs di Banjarmasin - Umi Risia; Aslamiah Aslamiah; Novitawati Novitawati (UNIB Press, 2024)
Social emotional development in early childhood aims to help children grow into emotionally healthy, socially resilient individuals, and contribute positively to society. The research focuses on the principal's policy strategy, the implementation of learning, the involvement of parents or the community, and the use of the environment as a learning resource in social-emotional development. The research design uses a descriptive qualitative approach, with a multi-site design with data collection through interviews, observations and documentation. The results of the research obtained on social-emotional development strategies in kindergarten 1) focus on character development, 2) Varied learning methods, adaptive strategies, and, regular evaluation and appropriate use of learning media, 3) Effective communication, active involvement of parents, and ensuring continuous learning programs at home, cooperation with external organizations and solutions to obstacles demonstrate their commitment to providing a holistic and supportive educational environment for children, 4) a supportive physical and natural environment, providing safe and enjoyable facilities and infrastructure, using various learning media to enrich children's learning experience. This holistic approach creates a learning environment that is conducive to the child's overall social and emotional development.